Toward the Millennium, Messianic Expectations from the Bible to Waco. - Peter Schäfer (Author); Mark Cohen (Editor) (Numen Book Series, 1998)
This collection of 16 articles represents a selection of the papers delivered in the course of a seminar (1995-1996) at the Institute for Advanced Study in Princeton and its concluding joint symposium held at the Institute and Princeton University. Wide-ranging in scope, the volume covers messianic expectations from biblical times up to modern and contemporaneous adaptations, whereby the focus lies on the messianic concept within Judaism: diversity and variety of messianic expectations in antiquity; messianic movements at the time of the Crusades and around the fifth millennium (1240); the 'Pseudo'-Messiah Sabbatai Avi in the early modern period; the philosophers Hermann Cohen, Franz Rosenzweig and Walter Benjamin with respect to their thinking about messianism as well as the Lubavitch movement. Also included are investigations on pagan Graeco-Roman writings and messianic strands in the medieval and baroque Christian context. The section on the modern period contains contributions dealing with the Ahmaddiyya movement in India, messianic currents in the socio-political culture of the Weimar Republic as well as certain messianic aspects in the very recent so-called Branch Davidian community in Waco, Texas. The broad spectrum of stimulating analyses provides a fresh re-evaluation of an apparently timeless phenomenon.